Clinical Efficacy of Cortex Daphnes (Zushima) Patch in Patients With Symptomatic Knee Osteoarthritis: A Multicenter Non-Inferiority Randomized Controlled Clinical Trial - Li, Yan-Ting; Jiao, Juan; Zhang, Yi; Huang, Ci-Bo; Wang, Hai-Dong; Wang, Bei; Su, Xiao; Song, Hui; Zhao, Mian-Song; Jiang, De-Xun; Wang, Jia-Qiang; Jiang, Quan (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is imposing substantial burdens on individuals and society with the aging population. Cortex Daphnes patch is widely used for symptomatic knee OA in China with a satisfying clinical efficacy; however, there is scant clinical evidence supporting its use. To evaluate its efficacy, we conducted a multicenter, non-inferiority, randomized, parallel-group study comparing Cortex Daphnes patch with topical nonsteroidal anti-inflammatory drugs in patients with knee OA (NCT02770950). A total of 264 symptomatic knee OA patients were treated with Cortex Daphnes or indomethacin cataplasms applied to affected sites once daily for 2 weeks. The primary outcome was improvement in knee pain on walking as assessed using a visual analog scale (VAS). The non-inferiority margin based on the full analysis population was set as –5 mm on the pain VAS. The secondary outcomes were changes of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) total score, WOMAC scores for pain, function and stiffness, the 36-item Short Form Health Survey (SF-36), and global assessment of knees by the patients. Responder rates for pain VAS, WOMAC total score and WOMAC pain were also included in the secondary outcomes. The Cortex Daphnes patch was non-inferior to indomethacin cataplasms for the primary outcome with a group difference (Cortex Daphnes patch–indomethacin cataplasm) of 2.1 mm (95% confidence interval: –2.1 to 6.4); similar results were found in the per-protocol population. For all other outcomes, no significant differences were found in the full analysis set or in the per-protocol analysis set, except the responder rates for WOMAC pain was higher in the Cortex Daphnes patch group than in the indomethacin cataplasm group (78.4% vs. 64.7%, p = 0.022) in the per-protocol analysis set. Overall, 28.8% patients in the Cortex Daphnes patch group and 9.8% in the indomethacin cataplasm group reported treatment-related adverse events, the vast majority of which were mild-to-moderate skin irritation, resulting in only 3.8% and 0.8% of patients dropping out, respectively. The Cortex Daphnes patch, which provides satisfactory analgesic efficacy and enhances the physical function of the knee, as well as improving quality of life, may be a promising alternative to knee OA.